Răspuns :
Se verifica relatia;
xy-3(x+y)+12 = (x-3) (y-3)+3
Atunci
x*3= (x-3)(3-3)+3=3
3*x=(3-3)(x-3)+3=0
sau verifici ca e comutativa si nu faci decat prima, adica doar x*3
x compus x=x
(x-3)(x-3)+3=x
(x-3)(x-3)=x-3
(x-3)(x-3)-(x-3)=0
(x-3)(x-3-1)=0
(x-3)(x-4)=0
x1=3
x2=4
xy-3(x+y)+12 = (x-3) (y-3)+3
Atunci
x*3= (x-3)(3-3)+3=3
3*x=(3-3)(x-3)+3=0
sau verifici ca e comutativa si nu faci decat prima, adica doar x*3
x compus x=x
(x-3)(x-3)+3=x
(x-3)(x-3)=x-3
(x-3)(x-3)-(x-3)=0
(x-3)(x-3-1)=0
(x-3)(x-4)=0
x1=3
x2=4